Exploration of Wild Edible Plants Used as Food by Gaddis-A Tribal Community of the Western Himalaya - Arti Thakur; Somvir Singh; Sunil Puri (The Scientific World Journal)
A survey of wild edible plants of Gaddi tribes of Himachal Pradesh was carried out in Chamba and Kangra districts of Himachal Pradesh located in Western Himalayas. The inhabitants subsisted primarily on pastoralism and agriculture and have traditional knowledge on wild edible plants. A total of 49 edible plants belonging to 24 families were recorded in the study area. These were commonly used as vegetables, fruits, spices, and chutney. Nearly half of the species belong to Polygonaceae and Rosaceae families. Herbs, shrubs, climbers, and trees form the habit of these plants. The highest proportion of edible species were herbs (29) followed by trees (10), shrubs (8), climber (1), and Morchella esculenta (fungi) (1).